Neonatal outcomes related to maternal SARS-CoV-2 infection in French Guiana: A case-control study. Issue 7 (July 2022) - Elenga, N.; Wandji, M.-J.; Siban, J.; Nacher, M.; Demar, M.
Abstract: Background: This study aims to assess the neonatal outcomes related to maternal SARS-COV-2 infection. Methods: In this study, we identified newborns born between May 14 and August 31, 2020, to mothers who were PCR-SRAS-CoV-2 positive at the time of delivery. From the cohort of 974 infants, we performed a nested case-control study. Results: During the study period, 133 (13.7%) mothers were positive for SARS‐CoV‐2. Among the 35 pregnant women with COVID-19 symptoms (26.3%), cough was the most common symptom, present in half of the cases. Four of them have progressed to critical pneumonia requiring transfer to intensive care unit. The neonates from mothers with positive SARS-CoV-2-RT-PCR, were routinely tested for COVID-19 within the first 24 h after labor, and 3 other newborns tested in the presence of symptoms. There was no significant difference between the two groups with respect to preterm birth, meconium-stained amniotic fluid distress, and neonatal asphyxia. Most infants were breastfed at birth, regardless of their mothers' COVID-19 status. In COVID-19-positive pregnant women admitted to intensive care unit, the proportion of preterm births (OR=12.5 [1.7–90.5]), fetal death in utero (OR=25.9 [2.2–305]) and admission in neonatal intensive care unit admission (OR=13.4 [3.0–60]), appeared higher than the controls. No maternal deaths were recorded. Conclusions: Our data suggest little neonatal morbidity associated with maternal COVID-19, except for those born to mothers admitted to intensive care unit. However, under breastfeeding conditions with rigorous hygiene precautions and parental education, the risk of transmission of SARS-COV-2 virus to the newborn was very low.